Exploration of passive hardness of hardened simple steel in conditions of abrasive chafing - Kudrin, A. J.; Labunets, V. F.; Vishnevsky, O. A. (Proceedings of National Aviation University (archive), 2003)
Results of explorations of a surface hardening and abrasive hardness effect on abrasive passive hardness of simple steel are presented